Using phage Lytic Enzymes to Control Pathogenic Bacteria - Fischetti Vincent A (BMC Oral Health, 2006)
Abstract Our laboratory has developed phage lytic enzymes to prevent infection by specifically destroying disease bacteria on mucous membranes and in blood. Enzymes specific for S. pneumoniae and S. pyogenes have been developed to be used nasally and orally to control these organisms in environments such as hospitals and nursing homes to prevent or markedly reduce serious infections by these pathogens. In addition, a B. anthracis-specific enzyme was developed to kill the vegetative forms of these bacteria in the blood of infected individuals. In animal studies, >80% of mice colonized mucosally or infected intravenously with pathogenic bacteria were decolonized or survived after a single enzyme treatment delivered to the same site of colonization or infection.